Pure ones: the WˁB AND WˁBT from the old Kingdom to the end of the middle kingdom - Wilson, Amy (AUC Knowledge Fountain, 2014)
This thesis explores the development of the wˁb-title from the Old Kingdom to the end of the Middle Kingdom. During the Old Kingdom, 59% of title-holders are linked to the royal mortuary cult, many of whom were promoted to the upper-ranking office of ḥm-nṯr. Of all of the known title-holders of the Old Kingdom, 46% were promoted to ḥm-nṯr. Although some wˁb.w continue to be linked to the royal mortuary cult in the Middle Kingdom, the majority of title-holders are now linked to the cult of a deity. Few wˁb-priests were promoted to (or served within) other priestly grades, e.g. ḥm-nṯr, ḥm-k3, ẖry-ḥbt, or s(t)m-priest. There is, however, a remarkable increase (4%) in the number of female title-holders during the Middle Kingdom. An investigation into issues of heredity and transfer of office revealed that the most common filial relationships for all historical periods were father-and-son and brother-and-brother. The information compiled within this study provides insight into the role of the wˁb in cult and society from the Old Kingdom to the end of the Middle Kingdom. A chronological index, containing the names and title-strings of 524 men and women that held this title from the 3rd Dynasty to the 13th Dynasty concludes this study.